Event-Triggered Distributed Adaptive Fixed-Time Formation Control of QUAVs With Input Constraints - Xu, Hui; Cui, Guozeng; Ma, Qian; Li, Ze (IEEE transactions on vehicular technology, 2024)
This paper considers the distributed fixed-time formation control problem of multiple quad-rotor unmanned aerial vehicles (QUAVs) subject to input constraints. With an emphasis on resolving the "explosion of complexity" problem, the fixed-time command filter is constructed. Aiming at eliminating the impact of filtering errors, the error compensation signals based on fractional-power are designed. Additionally, the problem of singularity is skillfully addressed with the help of the piecewise function. To compensate for the influence of input constraints, the auxiliary signal with fixed-time convergence is devised. By incorporating the event-triggered control mechanism into the command filtered backstepping design process, an event-triggered distributed adaptive fixed-time formation control algorithm for multiple QUAVs is developed. It is strictly proved that all closed-loop signals are fixed-time bounded and the formation tracking errors are driven into a small neighborhood of the origin within a fixed time. Finally, two simulation examples demonstrate the effectiveness of the proposed fixed-time formation control scheme.